A contemporary comprehensive economic science : the economic thought and legacy of Maffeo Pantaleoni - Spalletti, Stefano; Spigarelli, Francesca (Routledge, 2026)
Covering Maffeo Pantaleoni's key areas of contribution to economics, this book provides a comprehensive study of one of the foremost economic thinkers of the late 19th and early 20th centuries. Called the 'prince' of Italian economists by Piero Sraffa, among others, Maffeo Pantaleoni (1857-1924) was an original and innovative thinker but also bizarre and extravagant. As a result he did not produce an inherently continuous and systematic work, but his contributions oscillate between a shifting idealism and heterogeneous operational criteria. Contrasting with the specialisation which pervades the economic sciences today, rereading Pantaleoni one hundred years after his death, it is clear that he excelled in 'pure' as much as in 'applied' economics, in public economics as in statistical or historical-economic studies. Overall, his expertise spanned fields of economics that are now considered disaggregated and distant from each other. Thus, the Pantaleonian spirit, which was innovative and completist and could not be confined within any enclosure, was lost a century ago. This volume brings together a group of specialists capable of identifying the many points of contact between Pantaleoni's multiform thought and the disciplinary plurality of his economics - thus providing 'A Complete Economic Science' of which Pantaleoni would be proud.The book will be of interest to economists, readers in history of economic thought, intellectual history, Italian history more broadly, and scholars with diverse profiles of interest.
Keywords: Pantaleoni, Maffeo, -- 1857-1924.; Economics -- History -- 19th century.; Economics -- History -- 20th century.; 1800-1899; 1900-1999; elektronické knihy; electronic books